Environmental predictors of the occurrence of ground water mosquito immatures in the Paraná Lower Delta, Argentina - Cardo, María Victoria (2011)
Characterizing mosquito larval habitats is essential for understanding the complex interactions between immatures and the biotic and abiotic components of their environment. Using generalized linear mixed models, we studied the environmental predictors of the presence of three ubiquitous mosquito species breeding in ground water habitats in the Paraná Lower Delta, Argentina. During a year-round survey, 34.1% of the 419 ground water habitats inspected were positive for either Culex dolosus s.l. (Lynch Arribálzaga 1891), Aedes crinifer (Theobald 1903), or Culex intrincatus Brèthes 1916. Univariate analysis showed that the former two occurred throughout the year, whereas the latter during the summer and fall. Ae. crinifer and Cx. intrincatus were more frequently collected in secondary forests, whereas Cx. dolosus s.l. was homogeneously distributed among land uses. Best generalized linear mixed models included the sampling period and landscape variables in different combinations for each species. Spatial dependence of the data was evident for Cx. dolosus s.l. and Ae. crinifer. Our results showed that the most widespread species presented different spatio-temporal distribution patterns, related with land use, anthropic intervention, and seasonality, highlighting the complexity of the wetland under study. This methodological approach could aid in the selection of priority areas for vector control and disease risk management.